Social Protection in the Face of Climate Change : Targeting Principles and Financing Mechanisms - Carter, Michael R.; Janzen, Sarah A. (World Bank, Washington, DC, 2015)
Climate risk is an important driver of long-term poverty dynamics, especially in rural regions. This paper builds a dynamic, multi-generation household model of consumption, accumulation, and risk management to draw out the full consequences of exposure to climate risk. The model incorporates the long-term impacts of consumption shortfalls, induced by the optimal “asset smoothing” coping behavior of the vulnerable, on the human capital and long-term wellbeing of families. The analysis shows that the long-term level and depth of poverty can be improved by incorporating elements of “vulnerability-targeted social protection” into a conventional system of social protection. The paper also explores the degree to which vulnerability-targeted social protection can be implemented through a subsidized insurance mechanism. The analysis shows that insurance-based vulnerability-targeted social protection dominates (in economic growth and poverty reduction measures) both in-kind transfer mechanisms and vulnerability-targeted protection paid for using a public budget. The relative gains brought about by this scheme of insurance-augmented social protection increase—at least for a while—under climate change scenarios. However, if climate change becomes too severe, then even this novel form of social protection loses its ability to stabilize the extent and depth of poverty.